A differential medium for the enumeration of the spollage yeast zygosaccharomyces bailii in wine - Schuller, Dorit Elisabeth (2000)
A collection of yeasts, isolated mostly from spoiled wines, was used in order to develop a differential medium for Zygosaccharomyces bailii. The 118 selected strains of 21 species differed in their origin and resistance to preservatives and belonged to the genera Pichia, Torulaspora, Dekkera, Debaryomyces, Saccharomycodes, Issatchenkia, Kluyveromyces, Kloeckera, Lodderomyces, Schizosaccharomyces, Rhodotorula, Saccharomyces and Zygosaccharomyces. The design of the culture medium was based on the different ability of the various yeast species to grow in a mineral medium with glucose and formic acid (mixed-substrate medium) as the only carbon and energy sources and supplemented with an acid-base indicator. By manipulating the concentration of the acid and the sugar it was possible to select conditions where only Z. bailii strains gave rise to alkalization, associated with a color change of the medium (positive response). The final composition of the mixed medium was adjusted as a compromise between the percentage of recovery and selectivity for Z. bailii. This was accomplished by the use of pure or mixed cultures of the yeast strains and applying the membrane filtration methodology. The microbiological analysis of two samples of contaminated "Vinho Verde" showed that the new medium can be considered as a differential medium to distinguish Z. bailii from other contaminating yeasts, having potential application in the microbiological control of wines and probably other beverages and foods.